Adjustment of different results for mathematics examinations - Krylovas, Aleksandras; Raulynaitis, Juozas; Jaurienė, Janina (Lietuvos matematikos rinkinys, 2002)
The article deals with the adjustment of the evaluation of knowledge by different professors of mathematics.